Las primeras justificaciones griegas de la democracia - Gil, Luis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
Greek political thougth advanced its first justifications of democracy through Athenagoras of Syracuse (Thuc. VI 39), Aspasia in the Menexenos (Plat. Men. 236A-249A) and Protagoras in the Platonic dialogue with the same title (320A 322D). While Athenagoras’ common sense approach (issues are best grasped collectively) is genuinely democratic, the Aspasia’s one shows an aristocratic and racist penchant. Ισονομίσ and έλευθερία, both based in ίσογουομία, allowing citizens to choose the best men for government, are only to be found in ‘autochthon’ Athens, which has been able to preserve its εύγένεια in the course of time. According to this view, democracy is actually a sort of aristocracy based on the consent of people. Aspasia generalizes Thucydides’ judgement on the leadership of Pericles. On the other hand, the myth of Protagoras extends the possibility of a democratic system to all human kind, for Zeus has distributed αιδώς and δίκη in equal shares among every individual, when men attain the level of citizens, the highest of their biological and cultural evolution.